On the future role of the Security Council - Christian Schaller (Stiftung Wissenschaft und Politik (SWP), 2005)
In December 2004, the Secretary General of the United Nations issued the report of the High-level Panel on Threats, Challenges and Change, which was charged with examin-ing how to more effectively address current and future security threats through collective action. One of the report's central objectives is the strengthening of the Security Council. Whether an increase in the number of its members will actually occur and whether the Security Council will become more capable of action is uncertain. But one thing is clear: The Security Council will not only be concerned with traditional threats to state security. It will also have to face non-conventional threats to human security. (SWP-Comments / SWP)
Keywords: 320